Experimental simulation of rock burst using exploding wire method - Ong, Ming Er (Nanyang Technological University, 2021)
Many land-scarce cities are looking at subterranean space to increase land availability. The resulting deep underground excavations from this endeavour induced violent strain energy release from confined rocks, creating cracks and ejecting fragments, which is known as rock burst. This gives rise to many research experiments developing to better understand and mitigate this geohazard. To examine the impact of excavation by blasting on rock burst, a series of explosion tests were conducted. This experiment had simulated stress waves using the exploding wire method, with the uniaxial compression machine exerting axial load on the specimen. Strain gauges and acoustic emission sensors were used to record the results. It was concluded that a higher probability of a rock burst occurrence is associated with larger loading rate under the same explosion activity. These preliminary tests allow for new questions and tests to be conducted.